UTILIZATION OF CABBAGE WASTE (Brassica oleracea) AS A PRESERVATIVE OF PARROT FISH (Oreochromis sp) - M. Said Siregar; Misril Fuadi; Ainun , (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The  research on the utilization of cabbage (Brassica oleracea) waste as a preservative tilapia (Oreochromis sp) with RAL factorial method with 2 replications.The first factor is NaCl concentration (K) which consists of 4 levels, namely: K1 = 1%, K2 = 2%, 3% = K3, K4 = 4%. Factor II is storage time (L) which consists of 4 levels, namely: L1 = 2 days, L2 = 4 days, L3 = 6 days, L4 = 8 days. The parameters observed from the data analysis showed that NaCl concentration and storage time significantly affected the protein content, moisture content, organoleptic aroma, texture organoleptic tests, organoleptic color.Keywords: utilization, cabbage waste, preservative, parrot fish